ANALISIS RESPON SISTEM GETARAN PADA MESIN TORAK - Riri Sadiana (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2016)
Vibration is a phenomenon that could not be avoided from a working system engine, so does the piston engine (piston engine). Vibration in piston engine in normal limits certainly will not interfere or reduce engine performance, But for a long time, it can reduce comfort and precision performance of the machine. The mathematical model of the vibration system on piston engine is needed in this case, created a mathematical model that will be analyzed and described, so it can be used as an input or guidelines to determine when the technical measures in the field. Reference systems work piston engine in this study refers to the piston engine in general or on a two-wheeled vehicle (125 CC).